Studies on the Manner of Collateral Regeneration From Nerve Stem to Motor Endplate - Qi, Zhidan; Li, Dongdong; Li, Li; Meng, Dexuan; Deng, Jin; Jin, Bo; Gu, Xinyi; Wang, Shen; Huang, Chen; Yin, Xiaofeng (Frontiers in Physiology, 2022)
Despite recent evidence suggesting that nerve transfer techniques help improve clinical outcomes, the underlying manner by which collateral-regenerated nerve enters skeletal muscles to restore an organized pattern of the neuromuscular junction (NMJ) is unclear. To construct the animal models of collateral regeneration, the proximal peroneal nerve was fixed to the distal tibial nerve stump. Three months after surgery, the spatial distribution of motor endplates (MEPs) and corresponding in-muscle nerve branches in long flexor digitorum muscles were observed with tissue optical clearing combined with light-sheet microscopy in transgenic fluorescent mice. The results showed that the number of fibers in the proximal donor peroneal nerve was 415 ± 11, while regenerated nerve fibers in the distal tibial stump were 781 ± 43, which indicates a collateral regeneration ratio of 1.88. The spatial distribution of MEPs was restored to an organized pattern of the lamella, and the corresponding in-muscle nerve branches reverted to the normal manner such as after collateral regeneration. Beyond this, the numbers of MEPs dominated by the single distal nerve fiber were 25.58 ± 0.50 and 26.42 ± 0.94, respectively (n = 6, p > 0.05, collateral regeneration group vs. normal group). However, the numbers of distal-regenerated nerve fibers were less than those in normal control groups (781 ± 43 vs. 914 ± 55, n = 6, p < 0.05), and the number and perforations of MEPs were lower than those in normal control groups as such. In summary, this is the first study to show the manner of collateral regeneration of the peripheral nerve that the smaller proximal donor nerve can sprout more axonal buds to connect distal larger nerves and finally restore to an organized pattern of lamella dominated by corresponding in-muscle nerve branches.